PLGA nanoparticles double-decorated with a TAT peptide and folic acid to target Staphylococcus aureus - Andrade, Stéphanie (2025)
Treating bacterial infections has become increasingly difficult due to the rise in antibiotic-resistant bacterial strains. Strategies involving the targeted delivery of antibiotics have been proposed to minimize the administered antibiotic doses. This study aims to develop the first double-modified nanovehicle capable of increasing bacterial membranes permeability while specifically targeting Staphylococcus aureus, one of the foremost pathogens responsible for global mortality rates. Thus, polymeric NPs composed of poly(lactic-co-glycolic acid) (PLGA) were produced, and their surface was modified with TAT peptide to increase the membranes permeability and folic acid (FA) to direct the NPs to S. aureus. The nanosystem showed spherical morphology with sizes of 174 ± 4 nm, a monodisperse population (polydispersity index of 0.08 ± 0.02), and a zeta potential of 2.5 ± 0.1 mV. The NPs remained stable for up to four months during storage. Fluorescence-based flow cytometry analysis proved that the double modification of PLGA NPs increased the interaction of the NPs with S. aureus, with fluorescence increasing from 71 ± 3% to 87 ± 1%. The nanosystem slightly affected the growth curve of S. aureus by extending both the lag time (from 2.5 ± 0.2 to 2.88 ± 0.4 h) and the exponential phase, as evidenced by an increase in the half-maximum growth time (from 3.9 ± 0.2 to 4.4 ± 0.1 h). Furthermore, the nanocarrier showed no toxicity for human dermal fibroblast cells, maintaining a 100% cell viability at the highest concentration tested (100 µM). Therefore, the proposed FA/TAT-functionalized nanocarrier presented promising features to be successfully used as a delivery vehicle of antimicrobials to fight S. aureus.